Exploring the rising incidence of neuroendocrine tumors: A population‐based analysis of epidemiology, metastatic presentation, and outcomes. Issue 4 (13th October 2014) - Hallet, Julie; Law, Calvin How Lim; Cukier, Moises; Saskin, Refik; Liu, Ning; Singh, Simron
<x xml:space="preserve">Abstract</x> BACKGROUND An increased incidence of neuroendocrine tumors (NETs) has been reported worldwide, but the reasons underlying this rise have not been identified. By assessing patterns of metastatic presentation, this study sought to examine the epidemiologic characteristics of NETs and the contribution of early‐stage detection to the rising incidence. METHODS A population‐based retrospective cohort study was conducted with prospectively maintained databases linked at the Institute for Clinical Evaluative Sciences. Adult patients with a NET diagnosis from 1994 to 2009 in Ontario, Canada were included. The main outcomes included the overall and site‐specific incidence, proportion of metastatic disease, overall survival (OS), and recurrence‐free survival (RFS). RESULTS Five thousand six hundred nineteen NET cases were identified. The incidence of NETs increased from 2.48 to 5.86 per 100, 000 per year. Metastases were found in 20.8% at presentation and in another 38% after the initial diagnosis. The proportion of metastases at presentation decreased from 1994 to 2009 (from 29% to 13%). Therefore, although the incidence of all NETs increased, the overall incidence of metastases did not change (0.63‐0.69 per 100, 000 per year). The 10‐year OS rate was 46.5%, and the RFS rate was 64.6%. In addition to the primary tumor site, independent predictors of worse OS included an advanced age (P < .0001), male sex (P < .0001), a low socioeconomic status (P < .0001), and rural living (P = 0.049). CONCLUSIONS The incidence of NETs has markedly increased over the course of 15 years. This is the first study to provide evidence suggesting that the increase in the incidence of NETs may be due to increased detection. In addition to tumor characteristics, low income and rural residency portend worse survival for patients with NETs. Cancer 2015;121:589–597. © 2014 American Cancer Society.